(untitled) (Mustansiria Dental Journal, 2018)
Dental pulp tissue is a highly specialized conneclive tissue contains a formative and protective cells that can be affected easily by stimuli such as occlusal trauma subjected by occlusal overhang filling. Sixteen albino rats aged range (6-8 months) weight range (0.5-0.75 kg) were subjected the occlusal overhang filling made for upper first molar for 2 periods, and according the periods, rats divided in the 2 groups. Groups I (8rats) subjected for occlusal trauma for 2 weeks duration group II (8rats) subjected for occlusal trauma for 8 weeks duration. Histological evaluation have been done for 2.8 weeks using hematoxyline and eosin stain. Occlusal trauma for 2 weeks in group I showed wide irregular predentin formation will displacement in odontoblast cell. While in group II for 8 weeks duration, histological feature for pulp tissue showed hyalinization (50-95 μm) in length. Occlusal trauma for long period cause hyalinization of pulp tissue that negatively influence on endodontic treatment in future.